2010
DOI: 10.1200/jco.2009.25.0894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant CYP2D6 Inhibitor Use and Tamoxifen Adherence on Breast Cancer Recurrence in Early-Stage Breast Cancer

Abstract: This observational study did not show an association between concomitant CYP2D6 inhibitor use and breast cancer recurrence among patients treated with adjuvant tamoxifen despite the strong biologic rationale. This study shows, to the best of our knowledge for the first time, that poor tamoxifen adherence is associated with an increased risk of breast cancer events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 34 publications
8
93
4
3
Order By: Relevance
“…1). In line with others who investigated breast cancer outcome by adherence by means of a landmark analysis [14], a cutoff of 1 year was chosen because of a considerable proportion of nonpersistence but occurrence of few events within 1 year of follow-up. Moreover, we aimed to exclude bias resulting from nonpersistence because of switch issues in the sequential arm.…”
Section: Discussionmentioning
confidence: 99%
“…1). In line with others who investigated breast cancer outcome by adherence by means of a landmark analysis [14], a cutoff of 1 year was chosen because of a considerable proportion of nonpersistence but occurrence of few events within 1 year of follow-up. Moreover, we aimed to exclude bias resulting from nonpersistence because of switch issues in the sequential arm.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown that lack of complete adherence was associated with risks for mortality that were elevated by 10% and 49% during the treatment periods of 2.4 and 4.5 years, respectively (15,20). In a study with 12 years of follow-up, patients with 80% or higher adherence had a 26% lower risk for breast cancer recurrence, compared with patients with less than 80% adherence (21).…”
Section: Early Disease/adjuvant Therapymentioning
confidence: 99%
“…Nonadherence to adjuvant endocrine treatment has been associated with overall mortality and a shorter disease-free survival in patients with breast cancer (9,10). Previous publications suggest nonadherence as high as 23.6% after the first year of follow-up (11,12).…”
Section: Introductionmentioning
confidence: 99%